Mycoparasitic species of Sphaerellopsis, and allied lichenicolous and other genera - Thippawan Trakunyingcharoen (2018)
© 2014 International Mycological Association. Species of Sphaerellopsis (sexual morph Eudarluca) are well-known cosmopolitan mycoparasites occurring on a wide range of rusts. Although their potential role as biocontrol agents has received some attention, the molecular phylogeny of the genus has never been resolved. Based on morphology and DNA sequence data of the large subunit nuclear ribosomal RNA gene (LSU, 28S) and the internal transcribed spacers (ITS) and 5.8S rRNA gene of the nrDNA operon, the genus Sphaerellopsis is shown to belong to Leptosphaeriaceae in Dothideomycetes. Sphaerellopsis is circumscribed, and the sexually typified generic name Eudarluca treated as a synonym on the basis that Sphaerellopsis is more commonly used in literature, is the older generic name, and is the morph commonly encountered by plant pathologists in the field. A neotype is designated for Sphaerellopsis filum, and two new species are introduced, S. macroconidialis and S. paraphysata spp. nov. Species previously incorrectly placed in Sphaerellopsis are allocated to Neosphaerellopsis gen. nov. as N. thailandica, and to the genus Acrocalymma, as A. fici. The genus Rhizopycnis is nestled among species of Acrocalymma, and reduced to synonymy based on its morphology and DNA phylogeny, while Acrocalymmaceae is introduced as novel family to accommodate members of this genus in the Dothideomycetes. Furthermore, Sphaerellopsis proved to be phylogenetically closely allied to a lichenicolous complex of phoma-like taxa, for which the new genera Diederichomyces and Xenophoma are established. Several new combinations are introduced, namely D. xanthomendozae, D. ficuzzae, D. caloplacae, D. cladoniicola, D. foliaceiphila, and X. puncteliae combs. nov, while Paraphaeosphaeria parmeliae sp. nov. is newly described.